2022
DOI: 10.3390/foods12010120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Root Color and Tissue on Phytochemical Contents and Antioxidant Activities in Carrot Genotypes

Abstract: This study monitored changes in major carotenoids (lutein, ⍺-carotene, and β-carotene), free sugars (fructose, glucose, and sucrose), ascorbic acid, vitamin E, phytosterols (campesterol, stigmasterol, and β-sitosterol), fatty acid composition, total phenol content (TPC), total flavonoid content (TFC), total anthocyanin content, and antioxidant activities (AA); ferric-reducing antioxidant power (FRAP) and 2,2′-azino-bis (3-ethylbenzothiazoline-6sulfonic acid) [ABTS] assays, in the inner and outer root tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Phenolic and favonoid compounds are responsible for the high efciency of antioxidant activity because they act as electron donors to reactive oxygen species (ROS) and prevent biological molecules from oxidizing the chain reaction [68]. Similar relations between phenolic compounds and antioxidant activities were also demonstrated in Isodon rugosus calluses [69], Daucus carota roots [70], and Beta vulgaris leaves [71].…”
Section: Heatmap and Hca Showing The Growth And Phytochemicalmentioning
confidence: 81%
“…Phenolic and favonoid compounds are responsible for the high efciency of antioxidant activity because they act as electron donors to reactive oxygen species (ROS) and prevent biological molecules from oxidizing the chain reaction [68]. Similar relations between phenolic compounds and antioxidant activities were also demonstrated in Isodon rugosus calluses [69], Daucus carota roots [70], and Beta vulgaris leaves [71].…”
Section: Heatmap and Hca Showing The Growth And Phytochemicalmentioning
confidence: 81%
“…The total vitamin E content higher in the outer tissues compared to the inner tissues of almost all genotypes. Howeve the purple carrot genotype shows the highest total vitamin E content in the inner an outer tissues compared to all of the other carrot genotypes [42].…”
Section: Vitaminsmentioning
confidence: 85%
“…The high content of polyunsaturated fatty acids (PUFAs) in carrot roots has been associated with their health potential. It has been reported that PUFAs exhibit antioxidant, anti-inflammatory, and antipyretic effects [42,51]. Interestingly, it has been reported that, among PUFAs, falcarinol-type oxylipins exhibit cytotoxic and anticancer activities [9,50], as described in more detail below.…”
Section: Fatty Acids and Their Derivativesmentioning
confidence: 92%
“…A correlation analysis was conducted to examine the relationship between antioxidant active substances and antioxidant activity, aiming to comprehend the individual contributions of each antioxidant to the overall antioxidant activity. It is well established that genotypic factors have a substantial impact on antioxidants, 29 consequently influencing the correlation between antioxidants and antioxidant activity (Table 2).…”
Section: Correlation Analysis Between Antioxidant Compounds and Antio...mentioning
confidence: 99%